Comparison of potassium and sodium binding in vivo and in agarose samples using TQTPPI pulse sequence - Schepkin, Victor D.; Neubauer, Andreas; Nagel, Armin Michael; Budinger, Thomas F. (Journal of Magnetic Resonance, 2017)
Potassium and sodium specific binding in vivo were explored at 21.1T by triple quantum (TQ) magnetic resonance (MR) signals without filtration to achieve high sensitivities and precise quantifications. The pulse sequence used time proportional phase increments (TPPI). During simultaneous phase-time increments, it provided total single quantum (SQ) and TQ MR signals in the second dimension at single and triple quantum frequencies, respectively. The detection of both TQ and SQ signals was performed at identical experimental conditions and the resulting TQ signal equals 60±3% of the SQ signal when all ions experience sufficient time for binding. In a rat head in vivo the TQ percentage relative to SQ for potassium is 41.5±3% and for sodium is 16.1±1%. These percentages were compared to the matching values in an agarose tissue model with MR relaxation times similar to those of mammalian brain tissue. The sodium TQ signal in agarose samples decreased in the presence of potassium, suggesting a competitive binding of potassium relative to sodium ions for the same binding sites. The TQTPPI signals correspond to almost two times more effective binding of potassium than sodium. In vivo, up to 69% of total potassium and 27% of total sodium can be regarded as bound or experiencing an association time in the range of several milliseconds. Experimental data analyses show that more than half of the in vivo total sodium TQ signal could be from extracellular space, which is an important factor for quantification of intracellular MR signals.
EVALuna2:14663